2018
DOI: 10.1029/2018pa003363
|View full text |Cite
|
Sign up to set email alerts
|

Paleoproductivity and Stratification Across the Subarctic Pacific Over Glacial‐Interglacial Cycles

Abstract: In the Subarctic Pacific, variability in productivity on glacial‐interglacial timescales is often attributed to changes in stratification and nutrient delivery to the surface, but the mechanisms driving this relationship are poorly constrained. Records extending beyond the last glacial maximum from both the open ocean and the marginal seas are required to investigate the timing and magnitude of different influential processes through the full glacial cycle. In this study we generated 231Pa/230Th over 210,000 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 200 publications
(367 reference statements)
1
9
0
Order By: Relevance
“…However, the distinct peaks of CaCO 3 and Ba bio contents (Figures 3B,D) observed during interglacials correlated with minima in OC fluxes, indicating paleo-productivity decoupled from OC burial over the past 380 kyr. Under the impact of the formation and enhancement of NPIW in the glacial stages, whose penetration depth hindered the supply of upward macronutrients from deeper water to the euphotic zone (Kohfeld and Chase, 2011;Worne et al, 2019), the observed lower paleo-productivity was similar to other glacial-interglacial cyclic records in the North Pacific (Jaccard et al, 2005;Li et al, 2017;Costa et al, 2018a). Therefore, in the Northwest Pacific, paleo-productivity during glacial periods with the driver of less macronutrient supply from deeper waters (Li et al, 2017) was contrary to that in high nitrate and low chlorophyll (HNLC) areas such as the subantarctic zone, where Fe derived from dust input was the main driver (Martinez-Garcia et al, 2014;Thöle et al, 2019).…”
Section: Temporal Variations Of Organic Carbon Inputsupporting
confidence: 76%
“…However, the distinct peaks of CaCO 3 and Ba bio contents (Figures 3B,D) observed during interglacials correlated with minima in OC fluxes, indicating paleo-productivity decoupled from OC burial over the past 380 kyr. Under the impact of the formation and enhancement of NPIW in the glacial stages, whose penetration depth hindered the supply of upward macronutrients from deeper water to the euphotic zone (Kohfeld and Chase, 2011;Worne et al, 2019), the observed lower paleo-productivity was similar to other glacial-interglacial cyclic records in the North Pacific (Jaccard et al, 2005;Li et al, 2017;Costa et al, 2018a). Therefore, in the Northwest Pacific, paleo-productivity during glacial periods with the driver of less macronutrient supply from deeper waters (Li et al, 2017) was contrary to that in high nitrate and low chlorophyll (HNLC) areas such as the subantarctic zone, where Fe derived from dust input was the main driver (Martinez-Garcia et al, 2014;Thöle et al, 2019).…”
Section: Temporal Variations Of Organic Carbon Inputsupporting
confidence: 76%
“…However, the driving mechanisms for changes in productivity over longer time scales are not yet entirely understood. For example, to what extent the productivity was influenced by the complex interplay of atmosphere and ocean and their respective circulation patterns dependent on, e.g., sea ice formation, light limitation, wind strength, nutrient supply, and stratification (Haug and Sigman, 2009;Jaccard et al, 2010;Sigman et al, 2010;Sigman et al, 2021); Kawahata et al, 2000;Matsumoto et al, 2002;Brunelle et al, 2007;Shigemitsu et al, 2007;Jaccard et al, 2010;Nishioka et al, 2011;Costa et al, 2018;Sigman et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Proxy data suggest comparatively lower levels of primary productivity at high latitudes during glaciations. In contrast, the rates of upwelling and cooler temperatures at lower latitudes resulted in an increase in primary productivity (Costa et al, 2018;Foster & Sexton, 2014;Hernández-Almeida et al, 2019;Radi & De Vernal, 2008;E. Thomas et al, 1995).…”
Section: Introductionmentioning
confidence: 97%
“…Thomas et al, 1995). The primary productivity increased at high latitudes, and decreased at lower latitudes when global temperatures increased after the LGM (Costa et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation